The Hoffnung's Acoustics - Hoffnung, Gerard 1925-1959 (London The Hoffnung Partnership, 2000)
Hoffnung's last book, published two weeks after his death highlights a superb and highly developed sense of the purely ridiculous in musical fun. A matador entices a prancing grand piano into the bull-ring and a similar instrument, at the crack of the ring-leader's whip, rears on its back leg to its full magnificent height. In the section on Noises Hoffnung reaches dizzying heights as he puts sound on to paper. Discover exactly what a cadenza, a pizzicato, a thud, a ping or a dozen other sounds actually look like. Fantastic too isthe swarm of instruments forming the Tutti, a drawing which bears endless scrutiny. This last book of Hoffnung's must be the most memorable of them all.